UPAYA GURU PAI DALAM MENGEMBANGKAN KETERAMPILAN BERFIKIR TINGKAT TINGGI DI SMA N 1 KINALI - Dewita Purnama Sari; Muhiddinur Kamal; Wedra Aprison; Charles (Universitas Pahlawan Tuanku Tambusai, 2022)
This research was motivated by the author's curiosity from the efforts of PAI teachers in implementing HOTS at SMA N 1 Kinali. Because SMA N 1 Kinali already uses the 2013 curriculum, it is possible that the school does not implement HOTS-based learning or apply students' higher-order thinking skills. Because high-level thinking skills can be interpreted as an effort made by the teacher in improving students' thinking patterns to a higher level, able to think critically, creatively and able to solve a problem. Based on the author's observations that 1) students are still passive in the learning process and class activities are only dominated by smart children, 2) in making questions the teacher uses more questions that are applying or just writing so that the questions are analytical, evaluation and creative. rarely appears, 3) students' ability to think critically and creatively is still lacking, this can be seen when students carry out discussions depending on one person who is able to answer in their group. However, in terms of student scores, the category is sufficient. The type of research that the author does is descriptive qualitative. Methods of data collection is done by observation, interviews, and documentation. Informants in this study focused on PAI teachers as key informants while students and their surroundings as supporting informants. The results of this study indicate that the forms of PAI teachers' efforts in developing HOTS at SMA N 1 Kinali can be seen from the planning, implementation and evaluation forms applied in the school. lesson plans that must be prepared by the teacher are preparing materials/materials and formulating lesson plans. In the RPP there are several HOTS indicators such as analyzing, evaluating and creating, the application of these indicators can be seen from the learning objectives and the steps of the learning activities used. Furthermore, the implementation of learning is carried out using HOTS learning activities including the application of strategies such as models, methods and media that support various kinds such as critical thinking, creative thinking, collaboration, communication and literacy used by teachers when carrying out the learning process. Meanwhile, teacher evaluation uses various forms of questions and the assessment also varies. So the conclusion is, PAI teachers at SMA N 1 Kinali have been able to fully develop HOTS as desired in the 2013 and 21st century curriculum. Keyword: PAI Teachers' Business Forms in Developing HOTS